Doped Heterojunction Used in Quantum Dot Sensitized Solar Cell - Yanyan Gao; Xiaoping Zou; Zongbo Huang (International Journal of Photoenergy)
Incorporated foreign atoms into the quantum dots (QDs) used in heterojunction have always been a challenge for solar energy conversion. A foreign atom indium atom was incorporated into PbS/CdS QDs to prepare In-PbS/In-CdS heterojunction by successive ionic layer adsorption and reaction method which is a chemical method. Experimental results indicate that PbS or CdS has been doped with In by SILAR method; the concentration of PbS and CdS which was doped In atoms has no significantly increase or decrease. In addition, incorporating of Indium atoms has resulted in the lattice distortions or changes of PbS or CdS and improved the light harvest of heterojunction. Using this heterojunction, Pt counter electrode and polysulfide electrolyte, to fabricate quantum dot sensitized solar cells, the short circuit current density ballooned to 27.01 mA/cm2 from 13.61 mA/cm2 and the open circuit voltage was improved to 0.43 V from 0.37 V at the same time.